“Canada Needs All Our Food-Power”: Industrial Nutrition in Canada, 1941–1948 - Strikwerda, Eric (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
This article examines the political economy of nutrition as a state-sponsored strategy to extract greater productivity from industrial workers in both wartime and peacetime. During World War II, the state, together with its munitions-industry allies, broadly considered workers’ nutritional health as a critical component to achieving maximum wartime industrial production. Following the war, both the state and industry imagined the nutritional health of workers’ bodies as crucial to Canada’s postwar prosperity. Facilitating as well as frustrating these largely state-directed nutrition agendas was a combination of medico-scientific knowledge, the sometimes uncertain and unpredictable participation of both employers and workers, and wider national and international historical contexts.